Peranan Badan Permusyawaratan Desa dalam Pembentukan Peraturan Desa Mendalo Indah Nomor 02 Tahun 2018 tentang Pemungutan Sampah Berdasarkan Peraturan Menteri dalam Negeri Nomor 111 Tahun 2014 - Muhamad Afrizal; Arfa’i Arfa’i (Jurnal Hukum, Administrasi Publik dan Negara, 2025)
This study examines the role of the Village Consultative Body (BPD) in the formation of Mendalo Indah Village Regulation Number 02 of 2018 regarding Waste Collection, referring to Minister of Home Affairs Regulation Number 111 of 2014. Using an empirical juridical approach with a qualitative research method, the study was conducted in Mendalo Indah Village, Muaro Jambi Regency, Jambi Province. Data were collected through participatory observation, in-depth interviews with key stakeholders (including the Village Head, BPD Chair, and community leaders), and documentation. The findings indicate that while the BPD's role in forming village regulations is generally less than optimal, it has a more active role during the discussion and finalization of the draft regulations. However, the initial drafting and proposing stages are often initiated by the Village Head, with limited proactive involvement from the BPD. Key challenges identified include inadequate BPD human resources, limited understanding of their duties, and poor communication and coordination between the BPD, the Village Government, and other stakeholders. The study concludes that improving the BPD’s capacity, knowledge, and collaboration is essential for more effective participation in village regulation formation.